Collective funerary rites and in private rituals,religious or secular - Yoffe, Laura (2014)
My Docthoral Thesis carried out with religious subjects from different creeds and with non religious individuals found that participation in collective funerary rites and in private rituals –religious or secular - allow the mourners to say good bye and accept the death of their deceased loved ones (Páez et al., 2007)..Funerals and bereavement rituals allow the symbolic expression of feelings and thoughts, assist the mourners to cope with loss, and promote their recovery from bereavement (Pargament, 1997; Yoffe, 2012c.).